Handbook of water and energy management in food processing - Klemeš, Jiří Jaromír; Smith, Robin (Chemical engineer); Kim, Jin-Kuk (Woodhead Pub. ; CRC Press, 2008)
Annotation Effective management of water and energy use in food processing is essential, not least for legislative compliance and cost reduction. This major volume reviews techniques for improvements in efficiency of water and energy use and wastewater treatment in the food industry. Opening chapters provide an overview of key drivers for better management. The second part of the book reviews methods to improve efficiency, from good housekeeping procedures to advanced techniques such as heat recovery. Improvements in particular processes, such as chilling and refrigerated storage, are also discussed. Following chapters cover advances in wastewater treatment technology. The book concludes by focusing on specific industry sectors such as baking and brewing.
Keywords: Food processing plants -- Energy conservation.; Food processing plants -- Water-supply.; elektronické knihy; electronic books